Efficient and Robust Mechanism against Replay Sybil and Tampering Attacks in Wireless Sensor Networks based upon the AES in CTR mode - AHOUANDJINOU, SÈMÈVO ARNAUD ROLAND MARTIAL; Ametepe, Adote François-Xavier; EZIN, C. Eugène (My University, 2021)
The security of data transmitted through wireless sensor networks remains a challenge. These networks are vulnerable to attacks and subject to strong constraints, such as the energy autonomy, the computing capacity and data storage. We study three fearsome attacks easy to execute. These are tampering, replay and sybil attacks which compromise the integrity and confidentiality of data transmitted. For mitigating these attacks, we propose an efficient and robust mechanism using Advanced Encryption Standard in counter mode which we associate with a dynamic session key mechanism. For the same plaintext, we obtain several ciphertext at each establishment of communication session. Several tests are performed with ATMega and ARM Cortex-M3 microcontrollers. The results show a loss of synchronization and it is not possible to decrypt an encrypted message, which manifests by an over-encryption as soon as an attack attempt occurs. We performed the assessment about the proposed device, through its robustness, the cryptographic processes, the memory and the energy. So, we remark an execution time of 0.21 ms and 0.63 ms for encryption as opposed to 0.28 ms and 1.63 ms for decryption when using the Arduino Due and Arduino Uno. We check off an energy consumption of 0.97-0.32 joules at encryption and 3.03-1.12 joules at decryption for 64 kilobytes of data processed using microcontrollers Arduino.
Keywords: Advanced encryption standard; mode compteur; replay attack; sybil attack; tampering; attack; réseaux de capteurs sans fil